Filamentous viruses associated with mosaic disease of garlic in India - Y.S. AHLAWAT, D.K. GHOSH* and (Indian Phytopathology, 2002)
The viruses associated with mosaic disease of garlic (Allium sativum) in New Delhi and Tamil Nadu, India, were investigated. In experimental host range studies with 33 plant species belonging to 5 different families, the causal virus could only infect Chenopodium album, producing chlorotic local lesions on inoculated leaves. Aphis craccivora and Myzus persicae transmitted the virus non-persistently to C. album. The virus was purified from infected garlic leaves and measured 425-980X12 nm. The purified preparations had an A260/A280 value of 1.19. Polyclonal antiserum was produced in a rabbit which had a titre of 1/512 in the tube precipitin test and 1/1024 in immunosorbent electron microscopy. In DAS-ELISA, the optimum concentration of coating andconjugate IgG was 1Î¼g/ml and 1:1000 respectively. The viruses were serologically related or identical to carnation latent carlavirus (Italy and Netherlands), garlic common latent carlavirus (Germany) and shallot latent carlavirus (Germany and Netherlands), all carlaviruses suggesting a mixed infection of 3 serologically different viruses in the mosaic disease of garlic in India.